Disturbances of Ligand Potency and Enhanced Degradation of the Human Glycine Receptor at Affected Positions G160 and T162 Originally Identified in Patients Suffering from Hyperekplexia - Atak, Sinem; Langlhofer, Georg; Schaefer, Natascha; Kessler, Denise; Meiselbach, Heike; Delto, Carolyn; Schindelin, Hermann; Villmann, Carmen (Frontiers in Molecular Neuroscience, 2015)
Ligand-binding of Cys-loop receptors is determined by N-terminal extracellular loop structures from the plus as well as from the minus side of two adjacent subunits in the pentameric receptor complex. An aromatic residue in loop B of the glycine receptor (GlyR) undergoes direct interaction with the incoming ligand via cation-π interactions. Recently we showed that mutated residues in loop B identified from human patients suffering from hyperekplexia disturb ligand-binding. Here, we exchanged the affected human residues by amino acids found in related members of the Cys-loop receptor family to determine the effects of side chain volume for ion channel properties. GlyR variants were characterized in vitro following transfection into cell lines in order to analyze protein expression, trafficking, degradation and ion channel function. GlyR α1 G160 mutations significantly decrease glycine potency arguing for a positional effect on neighboring aromatic residues and consequently glycine-binding within the ligand-binding pocket. Disturbed glycinergic inhibition due to T162 α1 mutations is an additive effect of affected biogenesis and structural changes within the ligand-binding site. Protein trafficking from the ER towards ER-Golgi intermediate compartment, the secretory Golgi pathways and finally the cell surface is largely diminished, but still sufficient to deliver ion channels that are functional at least at high glycine concentrations. The majority of T162 mutant protein accumulates in the ER and is conducted to ER-associated proteasomal degradation. Hence, G160 is an important determinant during glycine binding. In contrast, T162 assigns primarily receptor biogenesis whereas exchanges in functionality are secondary effects thereof.